The New Learning Environment: Impact on Staff and Students - Simons, Ellen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
This paper focuses on the changes in education and their implication for the university library. The impact of Avans’s strategic educational vision on the design and lay-out of the buildings. Especially Xplora, the Learning Centre of Avans, will be described. The three locations of the Avans Learning Centre (opened up in 2006 and 2007) comprise a total of 2,000 student workplaces. The traditional library has changed into a multimedia learning centre and now resides under the Avans’s Learning and Innovation Centre. New buildings and a new organisational structure demand new working arrangements with faculty staff. The transformation from library to learning centre and especially the consequences for library staff will be focussed upon. All staff were offered a comprehensive training programme. In addition, information specialists were trained to improve their acquaintance with educational knowledge. The benefits derived from the cooperation between library staff and colleagues from other disciplines (e.g. educational consultants, e-learning consultants, multimedia staff etc.) within the Avans Learning and Innovation Centre will be described. The results of relevant student surveys will also be described. At the end some conclusions will be drawn based on four years of working with new buildings, new educational models, a new organisation, new working arrangements, etc.